Template for teaching and assessment of problem solving in introductory physics - E. W. Burkholder (American Physical Society, 2020)
We introduce a template to (i) scaffold the problem solving process for students in the physics 1 course, and (ii) serve as a generic rubric for measuring how expertlike students are in their problem solving. This template is based on empirical studies of the problem solving practices of expert scientists and engineers, unlike most existing templates which are based on prescriptive, theoretical descriptions of expert problem solving and are largely based on how experts solve textbook-style problems. However, there is still some overlap with existing problem solving templates. In study 1, we investigated the validity of the template for use in introductory physics in two ways, first, by analyzing the final exam solutions from a Physics 1 course, and second, by analyzing seven think-aloud cognitive interviews as successful introductory physics students worked to solve a challenging problem. The results show that use of the elements of the template is correlated with successful problem solving, the template follows successful students’ existing problem solving processes, and explicitly using the template in solving problems does not add additional cognitive load. In study 2, analysis of final exam solutions from a different introductory physics course shows that the relationship between template use and problem solving performance depends on the type and difficulty of the problem. In this work, we also identified some consistent difficulties of unsuccessful students in solving problems which suggests some ways to better teach physics problem solving.